2023
DOI: 10.14569/ijacsa.2023.0140410
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of You Only Look Once Networks for Vision-based Small Object Detection

Abstract: Small object detection is a challenging issue in computer vision-based algorithms. Although various methods have been investigated for common objects including person, car and others, small object are not addressed in this issue. Therefore, it is necessary to conduct more researches on them. This paper is focused on small object detection especially jewellery as current object detection methods suffer from low accuracy in this domain. This paper introduces a new dataset whose images were taken by a web camera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In a parallel investigation, Yang [18] conducted a comprehensive analysis comparing the performance of YOLOv5, YOLOv6, and YOLOv7 models. Interestingly, Yang's findings align closely with our own research, as he observed that the YOLOv6 model exhibited superior performance compared to its counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel investigation, Yang [18] conducted a comprehensive analysis comparing the performance of YOLOv5, YOLOv6, and YOLOv7 models. Interestingly, Yang's findings align closely with our own research, as he observed that the YOLOv6 model exhibited superior performance compared to its counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…YOLOv3 has also been used for other detections, for example, to detect pedestrians [11], vehicles [12], and road objects [13]. Another investigation compared YOLOv5, YOLOv6, and YOLOv7 for detecting small objects [14], while YOLOv7 was used for real-time weed detection [15]. Yung et al compared YOLOv5, YOLOv6, and YOLOv7 to detect safety helmets workers wear [16].…”
Section: Introductionmentioning
confidence: 99%